Telaah Kritis Pengaturan Pornografi di Indonesia dalam Perspektif Teori Kesetaraan Gender - Zham-Zham, Lelly Muridi; Sugiri, Bambang; Sulistyarini, Rachmi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to critically examine the regulation of pornography in Indonesia and review the regulation of pornography based on the theory of gender equality to be used as a basis for constructing laws in the future. This study used a conceptual approach and a statutory approach, with the type of normative legal research. The study results showed that the regulation related to pornography was regulated in Articles 282 to 283 of the Criminal Code regarding moral crimes, Article 4 of Law Number 44 of 2008 concerning Pornography, and Article 27 paragraph (1) of Law Number 19 of 2016 concerning Information and Electronic Transactions. Based on gender equality theory, the regulation of pornography was still vulnerable to harm women. The regulation of pornography in the future should contain rules with clear boundaries, tougher sanctions, and prioritizing the principle of gender equality.This study aimed to critically examine the regulation of pornography in Indonesia and review the regulation of pornography based on the theory of gender equality to be used as a basis for constructing laws in the future. This study used a conceptual approach and a statutory approach, with the type of normative legal research. The study results showed that the regulation related to pornography was regulated in Articles 282 to 283 of the Criminal Code regarding moral crimes, Article 4 of Law Number 44 of 2008 concerning Pornography, and Article 27 paragraph (1) of Law Number 19 of 2016 concerning Information and Electronic Transactions. Based on gender equality theory, the regulation of pornography was still vulnerable to harm women. The regulation of pornography in the future should contain rules with clear boundaries, tougher sanctions, and prioritizing the principle of gender equality.